2019
DOI: 10.1016/j.jad.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Neural connectivity during affect labeling predicts treatment response to psychological therapies for social anxiety disorder

Abstract: Amygdala-vlPFC connectivity during affect labeling predicted treatment responder status following CBT or ACT for social anxiety disorder. This suggests that the functioning of neural circuitry supporting emotion regulation capacities may be a 'gateway' to receiving benefit from psychological treatments. Future work should aim to replicate this effect in a larger sample and consider methods for enhancing functional connectivity within this circuitry as a potential treatment adjunct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Several reports have also highlighted functional or structural properties of the amygdala that are impacted by CBT, often correlating with improvements in clinical outcomes 22 , 26 – 28 . And, paralleling the Whitfield-Gabrielli et al findings studied here, two other studies have reported that different features of amygdala function predict SAD treatment response to CBT 29 , 30 . Yet, to our knowledge, none of these studies have been directly subjected to independent replication attempts.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Several reports have also highlighted functional or structural properties of the amygdala that are impacted by CBT, often correlating with improvements in clinical outcomes 22 , 26 – 28 . And, paralleling the Whitfield-Gabrielli et al findings studied here, two other studies have reported that different features of amygdala function predict SAD treatment response to CBT 29 , 30 . Yet, to our knowledge, none of these studies have been directly subjected to independent replication attempts.…”
supporting
confidence: 85%
“…We believe it is important to replicate precisely defined models 70 . For example, the amygdala is a sensible focus point for predictive models relating to SAD, given the large body of research indicating amygdala alterations in SAD and other anxiety disorders 24 , 25 , and with several studies reporting that features of amygdala function predict CBT response in SAD patients 1 , 29 , 30 . However, the particular predictive amygdala features have varied widely from study to study, often with little overlap.…”
Section: Discussionmentioning
confidence: 99%
“…19 (Fitzgerald et al, 2017b) Non-significant results 20 (Schmitt et al, 2016) Non-significant results 21 (Light et al, 2011) Non-significant results 22 (Yip et al, 2018) Non-significant results 23 (Hilland et al, 2018) Lacking healthy controls 24 Lacking healthy controls Table S1. List of excluded studies with reasons 25 (Contreras-Rodríguez et al, 2020) Lacking healthy controls 26 (Fitzgerald et al, 2019) Lacking healthy controls 27 (Schmitgen et al, 2019) Lacking healthy controls 28 (Gorka et al, 2019) Lacking healthy controls 29 (Klumpp et al, 2017b) Lacking healthy controls 30 (Fonzo et al, 2017b) Lacking healthy controls 31 (Fonzo et al, 2017a) Lacking healthy controls 32 (Klumpp et al, 2017a) Lacking healthy controls 33 (Reinecke et al, 2018) Lacking healthy controls 34 (Klumpp et al, 2017c) Lacking healthy controls 35 (Goldin et al, 2014) Lacking healthy controls 36 (Reinecke et al, 2014) Lacking healthy controls 37 (Brühl et al, 2013) Lacking healthy controls 38 (Goldin et al, 2013a) Lacking healthy controls 39 (Heller et al, 2013) Lacking healthy controls 40 (Goldin et al, 2013b) Lacking healthy controls 41 (Hermann et al, 2009) Lacking healthy controls 42 (Kanske et al, 2015) Non-whole-brain analysis 43 (Rabinak et al, 2014) Non-whole-brain analysis 44 (Kanske et al, 2012) Non-whole-brain analysis 45 (Lang et al, 2012) Non-whole-brain analysis 46 (Erk et al, 2010) Non-whole-brain analysis 47 (Douw et al, 2020) Non-whole-brain analysis 48 (Klumpp et al, 2019) Non-whole-brain analysis 49 (Jacob et al, 2019) Non-whole-brain analysis 50 (Young et al, 2019) Non-whole-brain analysis 51 (Zhang et al, 2018) Non-whole-brain analysis 52 …”
Section: Resultsmentioning
confidence: 99%
“…Depressed participants are able to upregulate or dampen the activity and connectivity of regions involved in emotional processing (e.g., amygdala) by focusing on memories or imagery while viewing their fMRI signals. Following this technique, patients show reduced depression symptoms and long‐term changes in the brain (Young et al, 2018). Another study found that depressed men exhibit greater functional connectivity between the amygdala and prefrontal areas following neurofeedback training; further, this connectivity change was positively associated with symptom improvement (Zotev, 2011).…”
Section: Emerging Work and Future Directions: Toward A Precision Mentmentioning
confidence: 99%